2009
DOI: 10.1080/01443610903147576
|View full text |Cite
|
Sign up to set email alerts
|

Metformin in the treatment of clomiphene citrate-resistant women with polycystic ovary syndrome undergoingin vitrofertilisation treatment: A randomised controlled trial

Abstract: This study was conducted to determine the efficacy of metformin vs placebo in women with polycystic ovary syndrome (PCOS) undergoing IVF treatment. A total of 66 CC-resistant patients were studied prospectively. The women were randomly assigned to receive 850 mg of metformin (n = 34) or placebo (n = 32) twice daily that started 1 month before commencing the IVF treatment and continued to the day of the pregnancy test. Compared with the metformin-treated group, women who received a placebo had a significant inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 25 publications
1
48
1
1
Order By: Relevance
“…We reported that 87 % of cycles prescribe between 1500 and 2000 mg/day of metformin. Similar dose distribution was also demonstrated among various major randomized controlled trials, with the majority using between 1500 and 2000 mg/day of metformin [10][11][12][13][14][15][16][17][18][19]. Regardless, in Palombo's meta-analysis, when the studies were stratified by high dose (>1000 mg/day) and low dose (≤1000 mg/day) treatment regimens, there was no significant difference in reproductive outcomes in PCOS women [21].…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…We reported that 87 % of cycles prescribe between 1500 and 2000 mg/day of metformin. Similar dose distribution was also demonstrated among various major randomized controlled trials, with the majority using between 1500 and 2000 mg/day of metformin [10][11][12][13][14][15][16][17][18][19]. Regardless, in Palombo's meta-analysis, when the studies were stratified by high dose (>1000 mg/day) and low dose (≤1000 mg/day) treatment regimens, there was no significant difference in reproductive outcomes in PCOS women [21].…”
Section: Discussionsupporting
confidence: 64%
“…However, analysis shows no significant effect on pregnancy and live birth rates among PCOS patients after these studies were categorized by long term pretreatment (>3 weeks), short term pretreatment (≤3 weeks), or no pretreatment, and by stopping time of metformin with hCG administration, oocyte retrieval and embryo transfer as endpoints [21]. A significant effect was observed when metformin was administered until 12 weeks of pregnancy, but the data was only obtained in one study [17,21]. Metformin dosages reported in our survey were similar to those used in current clinical research.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…There was moderate‐quality evidence, from 13 studies involving 1551 women, that showed no significant difference in using antagonist or agonist protocols for ovarian stimulation (RR = 1.02 (95% CI, 0.91–1.15), I 2 = 7%). Low‐quality evidence, from 12 studies involving 1004 women, further suggested that the administration of metformin has a positive effect on clinical pregnancy compared with placebo or no metformin (RR = 1.26 (95% CI, 1.04–1.53), I 2 = 24%). Low‐quality evidence further suggested that there was no clinical difference between ovulation induction and estradiol for endometrial preparation for FET.…”
Section: Resultsmentioning
confidence: 99%